MEMAHAMI SISWA SD MENGGUNAKAN APLIKASI WINDOWS: IMPLEMENTASI DEVELOPMENTTALY APPROPRIATE PRACTICE UNTUK PEMBELAJARAN YANG œBERPIHAK KEPADA MURID - Hendriani, Ani; Riyadi, Arie Rakhmat; Syaripudin, Tatang; Kurniasih, Kurniasih; Ginting, Lea Christina Br; Magistra, Ari Arasy (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Implementing the "Kurikulum Merdeka" emphasizes the importance of student-centered learning, meaning that teachers must understand student characteristics, including their developmental task profiles. Teachers can use Windows-based applications called ITP and ATP to achieve this understanding. These applications help teachers gain insights into student development, especially in elementary schools, as a way to apply the principles of Developmentally Appropriate Practice (DAP) in learning. This activity aims to enhance elementary school teachers' abilities to use the ITP and ATP applications to understand students as an initial implementation of DAP. The methods include online sessions to strengthen teachers' understanding of the philosophy of student-centered learning, DAP concepts, elementary student development characteristics, and the introduction and installation of the ATP application. Teachers then simulate data collection and processing with the application, followed by in-person meetings for discussion and reinforcement. Twenty-six elementary school teachers from Sukabumi Regency participated in this activity, which took place from June 15 to July 3, 2024. The results show an increased understanding of the philosophy of student-centered learning, DAP concepts, and the use of applications to comprehend student characteristics. The conclusion is that mastering these applications and underlying concepts can enhance elementary school teachers' competencies in applying DAP principles for student-centered learning.